Study on the mechanism of forming silver nanoparticles on micron-scale flake silver powder. (2nd October 2020) - Tang, Lin; Gan, Guoyou; Yu, Xianglei; Liu, Chengbin; Cheng, Junhua
Abstract: Due to the high conductivity and stability of silver, silver ink has been widely used in the field of printed electronics. However, since mechanical strain would cause the contact between key particles to be broken. Recently, higher requirements have been put on the bending resistance of silver paste. In this experiment, by preparing Ag NPs: Ag Flakes composite materials of 20:80 and 30:70 respectively, a new method for preparing stable modified flake silver powder is proposed, and the attachment and growth methods of Ag NPs reduced on micron flake silver powder is discussed. Flake silver powder, dispersant and reducing agent are added to the silver-ammonia complex, and the nano-silver particles are reduced on the flake silver powder by controlling the reaction conditions. When Ag + : Ag Flakes in the solution is 30:70, there is a clear interface between the silver particles and the silver flakes, and the size distribution range is between 10 and 100 nm; when Ag + : Ag Flakes is 20:80, the distance between the nano-silver particles and the silver plate crystal plane is about 0.222 nm and 0.260 nm, these spacings represent the (1–12) and (004) planes of Ag, respectively. The reduced silver particles grow on the surface of the silver sheet, the size is about 5 ∼ 60 nm, and form a sheet-point combination of shaped silver powder, which can be used to make conductive silver paste with cost and performance competitiveness. The reaction can be completed at room temperature (5 ∼ 25 °C) and atmospheric pressure (80 ∼ 100 kPa), the operation is simple, the reaction time is short, and it has a positive effect on the commercial production of printable highly conductive silver paste.